HUBUNGAN KEKUATAN OTOT LENGAN BAHU DAN KELENTURAN OTOT PUNGGUNG DENGAN HASIL TOLAK PELURU PADA SISWA PUTRA KELAS VIII SMP 26 PEKANBARU - Asri Asri; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : from observations of researchers, students of class VIII can not generate maximum repulsion, can be seen from the lack of flaws in the prefix while holding the bullet, bullet exit position, the arm strength and position of the body at the time refused. tujan in this study to look at the relationship of muscle strength and flexibility of the arm and shoulder muscles of the back with the shot put results on male students of class VIII junior high school 26 pekanbaru consisting of 20 male students. in this study samples were taken using a total sampling, which means that all the men population sampled as many as 20 people. Instruments in this research is to test muscle strength using a shoulder sleeve expanding test dynamometer, to test the flexibility of the back muscles using the sit and reach test. and to test shot-put (Y) using the results of shot put. Data were analyzed using product moment correlation simple and double, based on the results of research diperolel strength of arms and shoulders have a relationship with the shot put results on male students of class VIII junior high school 26 pekanbaru. and with the same relationship exists between the arm and shoulder muscle strength and flexibility back to the shot put results on male students of class VIII junior high school 26 pekanbaru.Keywords: Arm And Shoulder Muscle Strength, Muscle Tone Back, Shot Put Results